Implementation of Research-Based Modules in the Concept of Structure and Function Animal Tissue on Student’s Learning Outcomes - Ervina Dewi; Rahmi Agustina; Ridwandi (Postgraduate, University of Mataram, 2026)
The concept of the structure and function of animal tissues is considered an abstract concept in biology because students cannot directly observe concrete examples to enhance their understanding. Therefore, an innovation in the form of a research-based module specifically designed to help students understand the material is needed. This study aimed to analyze the effect of implementing a research-based module on the concept of the structure and function of animal tissues on students’ learning outcomes. This research employed a quasi-experimental method and Nonequivalent Control Group Design, involving two classes that a control class (conventional learning) and an experimental class (research-based module). Data collection was conducted through pre-tests and post-tests to measure students’ learning outcomes. The research data were analyzed using the Independent Sample t-Test at a significance level of 5%, while improvements in learning outcomes in both classes were analyzed using the N-Gain test. The results showed that the implementation of the research-based module significantly improved students’ learning outcomes (P < 0.05) compared to conventional learning. The average post-test score in the experimental class was 71.08, while in the control class it was 56.08, with a t-test value of 2.97 and a homogeneity value of 0.80. The N-Gain test in the control class was 0.30 (moderate category), whereas in the experimental class it was 0.52 (moderate category). Statistical analysis of the N-Gain values of both classes indicated no significant difference (P > 0.05). In conclusion, the implementation of a research-based module is highly suitable for teaching abstract concepts, as indicated by the improvement in students’ learning outcomes.